Cash on Delivery Payment System in Online Buying and Selling Perspective of Sharia Economic Law - Moh. Zarkasi; Erie Hariyanto (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2021)
Observing the phenomenon of the rise of online buying and selling with cash on delivery (COD) payment systems that are not following consumer satisfaction, this research aims to discuss the view of Sharia economic law in the process of online buying and selling with the COD payment system. This type of research is literature research, using qualitative descriptive methods. Its approach is through normative and empirical legal approaches in the form of case studies. The results of this study concluded that based on the propositions of the Qur’an and hadith and the opinions of fiqh scholars, basically doing business is allowed as long as there is no element of gambling, fraud, riba, gharar, and dharar. In the case of online buying and selling with the COD payment system, if the goods sold are halal, it is clear that the quality and quantity of goods are between those offered by the seller and those received by the buyer; the payment is no element of fraud and addition, except for the postage agreed at the beginning, then according to Sharia economic law, the law can (mubah). However, conversely, if the practice of buying and selling online with COD payments, there are elements of gharar (unclear goods), riba (additional price without replacement), tadlis (fraud), and dharar (danger) that have an impact on harming sellers or buyers, then the law is haram.